Effects of resin content, wax addition and particle sizes on the properties of eight year-old Petai Belalang (Leuceana Leucocephala) particleboard / Jamaludin Kasim … [et al.] - Kasim, Jamaludin; Yamani, Shaikh Abdul Karim; Wan Abdul Rahman, Wan Mohd Nazri; Zainudin, Ahmad Ikhsan; Mohd Radzi, Mohd Johan; Abdul Hamid, Mohd Hafizul (Universiti Teknologi MARA Cawangan Pahang, 2008)
Petai belalang was successfully used in the manufacture of urea formaldehyde particleboard at a target density of 700 kg/m3, resin content (8, 10 and 12%), 1% wax and with particle sizes of 1 and 2 mm and, with a board thickness of 12 mm. Increasing resin content increases the MOR, MOE, IB and improves the TS significantly. Wax also showed significant effects on MOR, IB and TS. Particle size does not influence the board properties.